Grouping techniques in an EFL classroom - Ramírez Salas, Marlene (2005)
This article focuses on the need for English language teachers to use group work as a means to foster communication among students.  The writer presents a definition of group work, its advantages and disadvantages, some activities for using group work and some grouping techniques created or adapted by the writer to illustrate the topic.   Este artículo manifiesta la importancia del trabajo grupal en el aula, para motivar la comunicación entre los estudiantes. Asimismo, presenta la definición de trabajo en grupo, sus ventajas, desventajas y algunas actividades y técnicas para formar grupos.